Pengaruh Model Pembelajaran Kooperatif tipe Make A Match terhadap Kemampuan Komunikasi Matematis Siswa - Juliana Sundari (Universitas Indraprasta PGRI, 2017)
The purpose of this research is to determine The Impacts of Cooperative Learning Method Type Make a Match on Student’s Mathematics Communication Skills empirically. The research was conducted on the students grade x of chemistry Industry technique at public SMK 1 Gunung Putri on 60 students. The method is used in the research is quasy experiment method and design for taking the sample is simple random sampling technique. The instrument for data collection in this research is essay test as much as 14 items about quadratic equation which validated empirically. Data analysis technique used t test which examined normality and homogenity. Based on liliefors test, the data is distribution normally, and the result of homogenity test by fisher test, the data’s varians is same and homogen. Based on hypothesis test, it can be concluded that there are significant impacts of cooperative learning model type make a match on student’s mathematics communication skills in quadratic equation.